SCHOOL PROMOTION MANAGEMENT AND INCREASING COMMUNITY MOTIVATION TO ENROLL IN HARAPAN BANDAR PULO PRIVATE MIDDLE SCHOOL - Sembiring Depari, Rizky; Mesiono; Neliwati (Pena Cendekia Insani, 2025)
This study investigates the implementation of school promotion management in increasing community motivation to enroll their children at Harapan Private Junior High School in Bandar Pulo, Langkat Regency. Using a qualitative approach, data were gathered through interviews, focus group discussions, observations, and documentation. The findings reveal that the school applies structured and consistent promotional strategies through digital platforms and print media, directly targeting elementary students and their parents. Regular dissemination of school activities strengthens this effort. The study concludes that systematic, digital-based promotion effectively enhances public trust and enrollment interest.